Pengaruh Persepsi Harga, Kualitas, Distribusi, dan Promosi terhadap Keputusan Pembelian Produk Air Kemasan Merek Laka-Laka di Lombok Tengah - Andini, Dwi Tesna (TSAQOFAH, 2021)
This study aims to analyze the effect of perceived price, quality, promotion, and distribution on purchasing decisions Laka-Laka mineral water. Based on the results of the t test, it shows that the perception of price has a significant influence on the decision to purchase Laka-Laka mineral water. The product quality variable has a significant influence on purchasing decisions for the purchase Laka-Laka mineral water. Promotions variables have a significant influence on purchasing decisions Laka-Laka brand mineral water. Variable distribution variable has a significant influence on purchasing decisions. Based on the results of the F Test is Perception Price, Quality, Promotion and Distribution have a positive and significant effect on the purchasing decision variables. Based on the result of coefficient determination that R square is 76,4. This show that the perception of price (X1), quality (X2), promotion (X3) and distribution (X4) have an influence on the purchasing decision variables at 76.4%. While the rest (100% – 76.4% = 23.6%) is influenced by other factors outside the research variables.